Pelatihan Pembuatan Jamu d alam Upaya Meningkatkan Imunitas Masyarakat Kelurahan Muara Fajar Timur Kecamatan Rumbai Pekanbaru - Desi Heltina; Amun Amri; Silvia Reni Yenti; Komalasari Komalasari; Evelyn Evelyn; Isna Rahma Dini (Unri Conference Series: Community Engagement, 2021)
In the midst of the health crisis due to the ongoing Covid-19 pandemic, traditional medicine is an alternative that can be used by the community to break the chain of transmission and maintain body immunity. Immunity is important during the Covid-19 pandemic. The better a person's immune system is to fight infection, the less likely a person is to get the disease. The community has a very important role in efforts to develop traditional health by utilizing medicinal plants. Ginger and Turmeric are types of medicinal plants that are widely used as kitchen spices, and have benefits for increasing the body's immunity. The content of cincol and zingiberen in ginger acts as an antioxidant that can improve the work of the immune system. While turmeric contains curcumin compounds which act as an antiviral. The purpose of this research is to provide skills to the people of Muara Fajar Timur Village in processing medicinal plants into herbal products that are delicious to consume, useful for increasing immunity, and have economic value. Activities are carried out by direct training methods and distribution of herbal products to the community. The result of this activity is that the community can understand and be able to make herbal medicine. The success of this activity can be seen from the responses in the form of questions and answers and discussions with the training participants, the high interest of participants in participating in the activity and the benefits derived from this activity. This shows that this activity has been successfully implemented in Muara Fajar Timur Village, Rumbai District, Pekanbaru.